ANALISIS PENERJEMAHAN KOSA KATA BERMUATAN BUDAYA DALAM NOVEL CHINMOKU - Dian Pramita Sugiarti (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2015)
ABSTRACT This paper entitled Analysis of Cultural Vocabularies Translation in Chinmoku’s Novel is mainly aimed at investigating how the procedure analysis of cultural vocabularies from Japanese text to Indonesian text and any changes during translation. This research used some book with analysis Chinmoku’s novel. Those books are used as reference in this paper because the books represent the cultural vocabulary translation. In this research the data source was collected by reading those book and choosing the words that represent the cultural vocabularies translation. Then, the data was analyzed by descriptive qualitative method and collect all data of cultural vocabularies translation. There are some theories used in analyzing the data, those are the theory of semantic is collect the meaning of Chinmoku’s novel, the theory of translation, translation should have a meaning that is close to the source language, specially for cultural vocabularies translation. These analysis would describe the results of the translation of vocabulary of cultural content ini the Chinmoku’s novel. Keywords: translation, vocabularies, extinguishers culture